MORALITY AND THE GLOBAL CAPITALIST ECONOMIC ORDER (2015)
Morality, a means of evaluating human conducts and institutions, is central to the realisation of human welfare in the Global Capitalist Economy (GCE), understood as an aggregate of the economic interrelations among all nations of the world. Studies that addressed the inadequacies of the GCE in the pursuit of human welfare focused largely on the socio-political and economic dimensions to the problem without paying sufficient attention to its moral foundation, located in the principle of Moral Egoism (ME). This study, therefore, proffered Enlightened Self-interest (ESi) as a more viable moral foundation that would render the GCE more beneficial to all its stakeholders. The study adopted Adam Smith’s theory of impartiality and John Rawls’ theory of original position, both of which affirmed that individual interest is best pursued when adequate attention is given to others’ interest. Seven texts in moral philosophy, including Adam Smith’s A Theory of Moral Sentiments (TMS), John Rawls’ A Theory of Justice (TJ) and Moses Oke’s Self-interest as the Ground of Moral Obligation (SGMO), and six in political economy, including Adam Smith’s The Wealth of Nations (WN), Joseph Stiglitz’s Globalization and Its Discontents (GD) and Milton Friedman’s Capitalism and Freedom (CF), were purposively selected for their relevance to the moral foundation of the GCE. Conceptual analysis was employed to clarify key concepts such as ME, GCE, and human welfare. Critical examination was used to show the inadequacies of ME as the moral foundation of the GCE. Reconstruction was employed to present ESi as an effective moral principle for enhancing human welfare in the GCE. Moral philosophy showed the defects of unbridled pursuit of self-interest and the need to regulate it by giving adequate consideration to the interest of others (TMS, TJ and SGMO). Moral Egoism is an inadequate foundational principle if the GCE would achieve its purpose of enhancing the welfare of all its stakeholders (TMS). The postulation of an invisible hand does not guarantee widespread welfare of all stakeholders in the GCE because it stresses that the pursuit of self-interest eventuates in unintended benefit for the entire society, contrary to human experience (GD). Alternatively, an adequate foundation is found in a reciprocal, other-regarding approach to self-interest (TMS and TJ). Economic practices based on ME, which affirms self-interest as the basis for morality, have not sufficiently facilitated human welfare despite the promises of the GCE (WN, GD and CF). This is obvious, for instance, in the widespread global poverty. Critical reflections revealed that by emphasising morally reciprocal actions, as against ME’s narrow pursuit of self-interest, ESi would promote an all-inclusive benefit in the GCE. Enlightened Self-interest can be propagated through moral education that makes people understand that their interests can only be effectively achieved if they give adequate consideration to the interests of others (SGMO). Moral Egoism’s narrow perspective to promoting self-interests contrasts Enlightened Self-interest’s mutuality of interests for all. Therefore, replacing Moral Egoism with Enlightened Self-interest can substantially promote the common good of all stakeholders in the Global Capitalist Economy.